2016
DOI: 10.4137/cpath.s40143
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene Mutations in Colorectal Polyps Identified in the Norwegian Colorectal Cancer Prevention (NORCCAP) Screening Study

Abstract: Data are limited on oncogene mutation frequencies in polyps from principally asymptomatic participants of population-based colorectal cancer screening studies. In this study, DNA from 204 polyps, 5 mm or larger, were collected from 176 participants of the NORCCAP screening study and analyzed for mutations in KRAS, BRAF, and PIK3CA including the rarely studied KRAS exons 3 and 4 mutations. KRAS mutations were identified in 23.0% of the lesions and were significantly associated with tubulovillous adenomas and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
1
13
1
Order By: Relevance
“…In our study, we linked precursor CRC lesions to a molecular pathway with the aim of determining whether this molecular signature could predict the development of advanced lesions at follow-up. As expected and according with previous studies, BRAF mutations were rarely found in conventional adenomas [ 21 – 24 ]. However, we found BRAF mutations in less than 40% of serrated lesions, which was clearly less frequent than previously reported for this type of polyps [ 25 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we linked precursor CRC lesions to a molecular pathway with the aim of determining whether this molecular signature could predict the development of advanced lesions at follow-up. As expected and according with previous studies, BRAF mutations were rarely found in conventional adenomas [ 21 – 24 ]. However, we found BRAF mutations in less than 40% of serrated lesions, which was clearly less frequent than previously reported for this type of polyps [ 25 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The KRAS mutations (approximately, 90%) was found with a high detection rate within exon 2 (codons 12 and 13) and exon 3 (codon 61). According to clinical studies among all most common codons 12 and 13 mutations, only (p.G12D), (p.G12V), and (p.G13D) missense mutations, were more frequently specified to individuals with resected advanced neoplasia and CRC . Taking into consideration the experimental data, only low frequency distribution of p.G12D was detected as most abundant mutation in all patients with colorectal sporadic adenomas, in contradiction to other reports, which have obviously stated a higher percentage of somatic KRAS mutations in codons 12 and 13.…”
Section: Discussioncontrasting
confidence: 60%
“…According to clinical studies among all most common codons 12 and 13 mutations, only (p.G12D), (p.G12V), and (p.G13D) missense mutations, were more frequently specified to individuals with resected advanced neoplasia and CRC. 17,18 Taking into consideration the experimental data, only low frequency distribution of p.G12D was detected as most abundant mutation in all patients with colorectal sporadic adenomas, 16 in contradiction to other reports, which have obviously stated a higher percentage of somatic KRAS mutations in codons 12 and 13. Nonetheless, our data in CRC patients (p.G12D; 36%) was approximately in accordance with the previously published report.…”
Section: Discussionmentioning
confidence: 69%
“…These occur in the proximal colon and are more likely to be missed during colonoscopies and lead to more aggressive forms of cancer [ 14 ]. Females were also found to have higher frequency of KRAS mutations in codon 12 than males, which again are associated with more advanced adenomas [ 42 ].…”
Section: Discussionmentioning
confidence: 99%